Cancer with low cathepsin D levels is susceptible to vacuolar (H+)‐ATPase inhibition. Issue 6 (20th May 2017) - Kitazawa, Satoshi; Nishizawa, Satoru; Nakagawa, Hideyuki; Funata, Masaaki; Nishimura, Kazuho; Soga, Tomoyoshi; Hara, Takahito
Abstract : Vacuolar (H + )‐ATPases (V‐ATPases) have important roles in the supply of nutrients to tumors by mediating autophagy and the endocytic uptake of extracellular fluids. Accordingly, V‐ATPases are attractive therapeutic targets for cancer. However, the clinical use of V‐ATPase inhibitors as anticancer drugs has not been realized, possibly owing to their high toxicity in humans. Inhibition of V‐ATPase may be an appropriate strategy in highly susceptible cancers. In this study, we explored markers of V‐ATPase inhibitor sensitivity. V‐ATPase inhibitors led to pH impairment in acidic intracellular compartments, suppression of macropinocytosis, and decreased intracellular amino acid levels. The sensitivity of cells to V‐ATPase inhibitors was correlated with low cathepsin D expression, and cancer cells showed increased sensitivity to V‐ATPase inhibitors after pretreatment with a cathepsin D inhibitor and siRNA targeting the cathepsin D gene ( CTSD ). In addition, V‐ATPase inhibitor treatment led to the induction of the amino acid starvation response, upregulation of endoplasmic reticulum stress markers, and suppression of mammalian target of rapamycin (mTOR) signaling in cells expressing low levels of cathepsin D. Some colorectal cancer patients showed the downregulation of cathepsin D in tumor tissues compared with matched normal tissues. These findings indicate that V‐ATPase inhibitors are promising therapeutic options for cancers with downregulated cathepsin D. Abstract : The sensitivity of cells to V‐ATPase inhibitors was correlated with low cathepsin D expression. V‐ATPase inhibitors are promising therapeutic options for cancers with downregulated cathepsin D.